Enhancing psychological safety in mental health services - Hunt, DF; Bailey, J; Lennox, BR; Crofts, M; Vincent, C (BioMed Central, 2021)
Background Psychological safety—speaking up about ideas and concerns, free from interpersonal risk—are essential to the high-risk environment, such as healthcare settings. Psychologically safe working is particularly important in mental health where recovery-oriented approaches rely on collaborative efforts of interprofessional teams to make complex decisions. Much research focuses on antecedents and outcomes associated with psychological safety, but little focus on the practical steps for how to increase psychological safety across and at different levels of a healthcare organisation.